Modelling for tensile strength of friction welded aluminium pipes by ANFIS. (4th June 2010) - Singh, Jagdev; Gill, Simranpreet Singh
In this study, fuzzy model has been proposed to predict the tensile strength of radial friction welded aluminium pipes. The model is of multi-input single-output (MISO) type having two inputs signals; rotational speed (RPM) and forge load and tensile strength as output. The adaptive neuro-fuzzy inference system (ANFIS) technique of fuzzy based systems for modelling and simulation of the complex systems has been employed. The performance of the model is authenticated by evaluating the predicted results with the practical results obtained by conducting the confirmation experiments. The proposed model can be used for intelligent online adaptive control mode.